INTEGRASI AGAMA DAN SAINS DALAM DUNIA POSTMODERN: PELUANG DAN TANTANGAN BAGI FILSAFAT ILMU - Shinta Adhelia Putri Sugiharto; Sidqi Ali; Munirul Abidin (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The integration of religion and science in the postmodern era has become a significant issue in the philosophy of science, particularly in response to epistemic pluralism, the weakening of singular truth claims, and the growing demand for knowledge that is both empirically grounded and ethically meaningful. This study examines the opportunities and challenges of integrating religion and science within a postmodern framework and analyzes its implications for contemporary philosophy of science. The discussion highlights a paradigm shift from a dichotomous and hierarchical relationship toward a dialogical and pluralistic model, focusing on epistemological boundaries, methodological validity, and conceptual frameworks of integration. This research employs an integrative literature review combined with hermeneutic analysis of key texts in philosophy of science, religious thought, and educational studies. The findings indicate that integrating religion and science has the potential to enrich the philosophy of science through a reflective and non-reductionist approach, particularly in addressing contemporary crises of meaning, ethics, and knowledge fragmentation. However, significant challenges remain, including divergent criteria of truth and the risk of epistemological simplification. This study conceptualizes integration as a dynamic and critical dialogical process rather than a fixed or final synthesis.